Sexual attractiveness shared by both sexes mediates same‐sex sexual behaviour in the parasitoid wasp Telenomus triptus. (1st July 2015) - Todoroki, Yusuke; Mochizuki, Ko; Numata, Hideharu
Abstract The mating behaviour of a quasi‐gregarious egg parasitoid Telenomus triptus Nixon (Hymenoptera: Platygastridae), which exploits egg masses of a stink bug Piezodorus hybneri (Heteroptera: Pentatomidae), is examined in the laboratory. In this parasitoid wasp, male adults that emerge earlier stay at the natal egg mass and mate with subsequently emerging females. In the present study, a male adult that encounters the emergence of another male always waits for it to egress, and then mounts the newly emerging male. To examine why males of T. triptus show same‐sex sexual behaviour, male adults are presented with a parasitized host egg mass or a freshly killed wasp. Male adults are observed to remain at host egg masses from which only male wasp(s) had emerged. In addition, male adults attempt to copulate with freshly killed young male wasps. It is suggested that newly emerging male wasps are targets of same‐sex sexual behaviour because they possess cues for male sexual behaviour similar to the cues of females. Both the sex and age of freshly killed wasps affect the frequency of the sexual behaviour of male adults: females are more attractive than males, although their attractiveness declines with age. When the mating opportunity is restricted to the natal egg mass, the costs of failing to notice newly emerging female adults should be extremely high. Therefore, males are forced not to discriminate the sex, resulting in same‐sex sexual behaviour.